2016
DOI: 10.1007/s00701-016-2996-9
|View full text |Cite
|
Sign up to set email alerts
|

Translabyrinthine vestibular neurectomy and simultaneous cochlear implant for Ménière’s disease

Abstract: In our preliminary report, translabyrinthine vestibular nerve section and simultaneous cochlear implant showed encouraging results in order to definitively control both vestibular and cochlear symptoms during the same therapeutic procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 68 publications
0
20
0
1
Order By: Relevance
“…Of 37 studies included, 32 (86.5%) studies were full manuscripts [8][9][10][11][12][13] and five (13.5%) were conference abstracts. [43][44][45][46][47] 21 (56.8%) papers were case series (more than one patient), [19][20][21][22][25][26][27][28][29][30]36,37,40,[43][44][45][46][47] 11 (29.7%) were case reports (one patient), 23,24,[30][31][32][33][34][35]38,39,41,42 and five (13.5%) were case-control studies (one or more comparison groups). [8][9][10][11][12] Twenty-five (67.6%) studies were based internationally and 12 (32.4%) studies were based in the United States (Table I).…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 37 studies included, 32 (86.5%) studies were full manuscripts [8][9][10][11][12][13] and five (13.5%) were conference abstracts. [43][44][45][46][47] 21 (56.8%) papers were case series (more than one patient), [19][20][21][22][25][26][27][28][29][30]36,37,40,[43][44][45][46][47] 11 (29.7%) were case reports (one patient), 23,24,[30][31][32][33][34][35]38,39,41,42 and five (13.5%) were case-control studies (one or more comparison groups). [8][9][10][11][12] Twenty-five (67.6%) studies were based internationally and 12 (32.4%) studies were based in the United States (Table I).…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…Thirty-five (94.6%) studies reported preoperative and postoperative PTA for 188 patients in implanted ears. While two of three studies reviewed (Canzi 2017 andDoobe 2005) individually found statistically significant improvements in PTA scores following CoI, there was no statistically significant difference in PTA with inclusion of Mukherjee 2017 (Fig. 3d).…”
Section: Pta Outcomesmentioning
confidence: 91%
“…27 Several studies have demonstrated that QOL scores for patients with MD poorly correlate with vertigo symptoms 29,30 or objective measures of vestibular pathology, such as calorics or posturography. 31 Although the AAOHNS-CHE introduced a functional assessment of patients with MD in 1972, 16 Gabra et al 21 Shea et al 26 Hu and Parnes 22 De Valck et al 18 Jung et al 23 Diaz et al 19…”
Section: Discussionmentioning
confidence: 99%
“…The initial literature search yielded 419 studies, of which 148 remained after duplicates were removed. The remaining studies were screened by abstract, which narrowed to 20 articles for full-text review; 11 studies [16][17][18][19][20][21][22][23][24][25][26] were included for review and analysis ( Figure 1). Risk-of-bias assessment for each study using the MINORS instrument is listed in Table 1.…”
Section: Literature Search and Risk-of-bias Assessmentmentioning
confidence: 99%
“…Devido ao reconhecimento de fala em ambiente ruidoso ser uma queixa frequente de usuários de AASI, se faz necessário na prática clínica uma avaliação que permita investigar o desempenho comunicativo em uma situação mais próxima da realidade, ou seja, em ambientes ruidosos. Deste modo, foram realizados diversos estudos com a finalidade de desenvolver testes capazes de avaliar a habilidade de reconhecimento de fala na presença de ruído em diversos idiomas (Canzi et al, 2016;Cooper & Cutts, 1971;Costa, 1998;Melo, Menezes, & Pacífico, 2017;Plomp & Mimpen, 1979). No Brasil foi desenvolvido um teste, Research, Society and Development, v. 9, n. 10, e059108352, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8352 validado, reconhecido e amplamente utilizado na clínica fonoaudiológica, especialmente em situações de protetização auditiva para avaliar situações de fala no silêncio e no ruído, intitulado Listas de Sentenças em Português (LSP) (Costa, 1998).…”
Section: Introductionunclassified